Transplacental Antibody Transfer of Respiratory Syncytial Virus Specific IgG in Non-Human Primate Mother-Infant Pairs - Michael P. Citron; Jessica McAnulty; Cheryl Callahan; Walter Knapp; Jane Fontenot; Pablo Morales; Jessica A. Flynn; Cameron M. Douglas; Amy S. Espeseth (Pathogens, 2021)
One approach to protect new-borns against respiratory syncytial virus (RSV) is to vaccinate pregnant women in the last trimester of pregnancy. The boosting of circulating antibodies which can be transferred to the foetus would offer immune protection against the virus and ultimately the disease. Since non-human primates (NHPs) have similar reproductive anatomy, physiology, and antibody architecture and kinetics to humans, we utilized this preclinical species to evaluate maternal immunization (MI) using an RSV F subunit vaccine. Three species of NHPs known for their ability to be infected with human RSV in experimental challenge studies were tested for RSV-specific antibodies. African green monkeys had the highest overall antibody levels of the old-world monkeys evaluated and they gave birth to offspring with anti-RSV titers that were proportional to their mother. These higher overall antibody levels are associated with greater durability found in their offspring. Immunization of RSV seropositive AGMs during late pregnancy boosts RSV titers, which consequentially results in significantly higher titers in the vaccinated new-borns compared to the new-borns of unvaccinated mothers. These findings, accomplished in small treatment group sizes, demonstrate a model that provides an efficient, resource sparing and translatable preclinical in vivo system for evaluating vaccine candidates for maternal immunization.